QUALITY IN HUMAN RESOURCE MANAGEMENT - Kizilova, T. M. (Science and Transport Progress, 2006)
In the article experience of western enterprises is described by the management by human capitals and the standard «Investors in people» is considered, setting the professional level of organizational development for achievement of businnes-aims of enterprise.